Research on the Value and Path of Family Art Education-Take Vocal Music Education as an Example - Hu, Mengying (Journal of Research in Vocational Education, 2024)
By discussing the application of vocal music education in family art education, this paper reveals the value and diversified implementation path of family art education. Family art education not only helps to improve children's cognitive, emotional and social skills, but also promotes the improvement of parent-child relationship through art forms. On the basis of relevant research at home and abroad, taking vocal music education as an example, we analyze the unique role of family art education and propose a feasible implementation path. The research believes that family art education can cultivate children's artistic literacy, innovation ability, self-confidence and social skills, contribute to the enhancement of family cohesion, and also provide theoretical and practical guidance for the promotion of art education in the family environment.